RECONSTRUCTION OF THE 217-YEAR (1791–2007) WROCŁAW AIR TEMPERATURE AND PRECIPITATION SERIES - Bryś, Krystyna; Bryś, Tadeusz (Bulletin of Geography. Physical Geography Series, 2010)
The authors present the results of a climatologic reconstruction of the 217-year series (1791–2007) of monthly average values of air temperature and monthly totals of precipitation in Wrocław (Breslau). The reconstruction is based on verified measurement (or observation) data from the Breslau-Sternwarte Observatory (1791–1930), which were completed (1931–2007) by reconstructing values calculated from measurement data from other meteorological stations in Wrocław. Only the data for 1945 were estimated from the values of Polish (Cracow, Gniezno, Puławy) and foreign (Berlin, Prague) stations. The problem of restoring the homogeneity of the available initial data was taken into consideration because there were changes in location and observation times. The data were verified by comparing the measured values, among others of temperature, with the data from the nearest as well as other meteorological stations in Warsaw, Berlin, Prague, Vienna, de Bilt. In relation to this, the problem of special and temporal anisotropy of relations between the values of analysed stations was discussed.